Intervenciones. - Chomsky, Noam (Haymarket Books, 2010)
Noam Chomsky says that the freedom to challenge power is not just an opportunity, it's a responsibility. For the past several years Chomsky has been writing essays for The New York Times Syndicate, which are translated here into Spanish.